Population-specific recombination sites within the human MHC region - Lam, T H (Nature Publishing Group, 2013)
Genetic rearrangement by recombination is one of the major driving forces for genome evolution, and recombination is known to occur in non-random, discreet recombination sites within the genome. Mapping of recombination sites has proved to be difficult, particularly, in the human MHC region that is complicated by both population variation and highly polymorphic HLA genes. To overcome these problems, HLA-typed individuals from three representative populations: Asian, European and African were used to generate phased HLA haplotypes. Extended haplotype homozygosity (EHH) plots constructed from the phased haplotype data revealed discreet EHH drops corresponding to recombination events and these signatures were observed to be different for each population. Surprisingly, the majority of recombination sites detected are unique to each population, rather than being common. Unique recombination sites account for 56.8% (21/37 of total sites) in the Asian cohort, 50.0% (15/30 sites) in Europeans and 63.2% (24/38 sites) in Africans. Validation carried out at a known sperm typing recombination site of 45 kb (HLA-F-telomeric) showed that EHH was an efficient method to narrow the recombination region to 826 bp, and this was further refined to 660 bp by resequencing. This approach significantly enhanced mapping of the genomic architecture within the human MHC, and will be useful in studies to identify disease risk genes.